S Strategi Penggunaan Media Digital untuk Kesehatan Mental Pelajar di SMA Al-Khairiyah Cilegon: Indonesia - Muhammad Nasir (Jurnal Pustaka Cendekia Pendidikan, 2025)
Mental health is a condition where a person is aware of and has the ability to overcome all forms of stress that occur in normal life in general, as a form and effort to create prosperity in living his daily life. Students who fall into the category of being very vulnerable to being exposed to and influenced by negative things brought by digital media have now become a very important issue. This research aims to understand how and determine effective strategies for using digital media to support the creation of student mental health at Al-Khairiyah Cilegon High School. This research uses a qualitative descriptive method with in-depth interviews and observations of students and teaching staff at Al-Khairiyah Cilegon High School. The research results show that digital media can provide positive support to students if used wisely with innovative strategies, such as digital education, providing time limits for use, and being directed to use digital media as learning tools, such as looking for educational, innovative and motivational content to foster enthusiasm. Study. However, the thing that still determines whether this strategy works is that it must be supervised and accompanied by parents and teachers at school.